Calibration and evaluation of PUF-PAS sampling rates across the Global Atmospheric Passive Sampling (GAPS) network. Issue 1 (2nd November 2017) - Herkert, Nicholas J.; Spak, Scott N.; Smith, Austen; Schuster, Jasmin K.; Harner, Tom; Martinez, Andres; Hornbuckle, Keri C.
Abstract : Here we present and evaluate a method to determine PUF-PAS sampling rates ( R S ), and the effective sampling volume ( V eff ), for gas-phase chemical compounds deployed anywhere in the world. Abstract : Passive air samplers equipped with polyurethane foam (PUF-PAS) are frequently used to measure persistent organic pollutants (POPs) in ambient air. Here we present and evaluate a method to determine sampling rates ( R S ), and the effective sampling volume ( V eff ), for gas-phase chemical compounds captured by a PUF-PAS sampler deployed anywhere in the world. The method uses a mathematical model that requires only publicly available hourly meteorological data, physical–chemical properties of the target compound, and the deployment dates. The predicted R S is calibrated from sampling rates determined from 5 depuration compounds ( 13 C PCB-9, 13 C PCB-15, 13 C PCB-32, PCB-30, and d6 -γ-HCH) injected in 82 samples from 24 sites deployed by the Global Atmospheric Passive Sampling (GAPS) network around the world. The dimensionless fitting parameter, gamma, was found to be constant at 0.267 when implementing the Integrated Surface Database (ISD) weather observations and 0.315 using the Modern Era Retrospective-Analysis for Research and Applications (MERRA) weather dataset. The model provided acceptable agreement between modelled and depuration determined sampling rates, with 13 C PCB-9, 13 C PCB-32, and d6 -γ-HCH having mean percent bias near zero (±6%) for both weather datasets (ISD and MERRA). The model provides inexpensive and reliable PUF-PAS gas-phase R S and V eff when depuration compounds produce unusual or suspect results and for sites where the use of depuration compounds is impractical, such as sites experiencing low average wind speeds, very cold temperatures, or remote locations.